2014
DOI: 10.1007/s00167-014-3018-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of neuromuscular risk factors for anterior cruciate ligament injury through tensiomyography in male soccer players

Abstract: Resistance to fatigue and muscle stiffness in the hamstring muscles may be risk factors for ACL injury in male soccer players. In addition, a predominant impairment in TMG characteristics of the quadriceps over hamstrings may indicate an altered muscular co-contraction (imbalance) between both muscle groups, which might be another risk factor for ACL injury in this population. These findings should be taken into account when screening athletes at high risk of ACL injury and also to design adequate prevention p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 43 publications
2
38
0
4
Order By: Relevance
“…1 y fig. 2), en donde los datos del J4 son más similares a datos reportados por estudios previos referentes a ligas profesionales de fútbol como Alentorn-Geli et al, (2014) y Álvarez-Díaz, et al, (2014b.…”
Section: Discussionunclassified
“…1 y fig. 2), en donde los datos del J4 son más similares a datos reportados por estudios previos referentes a ligas profesionales de fútbol como Alentorn-Geli et al, (2014) y Álvarez-Díaz, et al, (2014b.…”
Section: Discussionunclassified
“…Претпоставља се да су боље контрактилне карак-теристике мишића ВЛ последица чињенице да мишићи опружачи зглоба колена, којима припада мишић ВЛ, играју значајну улогу када су у питању мишићи доњих екстремитета и у великој мери по-државају кретање како у спорту тако и у свакод-невним активностима. Овај резултат је у складу са претходним истраживањима из ове области која су спроведена на сличном узорку и сличним мишићним групама, а чији резултати говоре у прилог чињеници да мишић ВЛ има краће Тc, Тs, Тr, Тd и мање Dm од других мишића прегибача и опружача колена (Pišot et al, 2008;Zagorc et al, 2010;Alentorn-Geli et al, 2014;Alvarez-Diaz et al, 2014; Rodriguez-Ruiz et al, 2014).…”
Section: дискусијаunclassified
“…Узорак спортиста је имао следеће дескриптивне карактеристике: Узраст = 25.7±4.1 година; ТВ = 182.1±8.8 цм; ТМ = 82.4±7.9 кг; БМИ = 24.8±1.8 кг/м², а узорак неспортиста: Узраст = 28.7±4.1 година; ТВ = 185.07±4.9 цм; ТМ = 85.6±5.4 кг; БМИ = 25.06±1.8 кг/м². Групу спортиста су чинили кошаркаши (2), одбојкаши (2), џудисти (2) и каратисти (11), док је група неспортиста била састављена од различитих студената Бео-градског универзитета који се нису систематски бавили спортско такмичарским активностима. Сви спортисти су се налазили у процесу редовног спортског тренинга, са такмичарским стажом у свом спорту од најмање 5 година и активно су се такмичили у вишим лигашким ранговима спорта који тренирају.…”
Section: метод узорак испитаникаunclassified
See 1 more Smart Citation
“…This measurement method has showed a high reliability and sensitivity to detecting changes in muscular reactions (Križaj, Šimunić, & Zagar, 2008;Rey et al, 2012b) and it has also been found to possess a high reliability to measure the following variables: contraction time (Tc), half-relaxation time (Tr), delay time (Td), sustain time (Ts), and maximum radial displacement of the muscle belly (Dm) in muscles vastus medialis, vastus lateralis, rectus femoris, and BF (Rey, Lago-Peñas, & Lago-Ballesteros, 2012a;Rey, Lago-Peñas, Lago-Ballesteros, & Casáis, 2012b;Carrasco, Sanudo, de Hoyo, Pradas, & Da Silva, 2011;Tous-Fajardo et al, 2010). Thus, the information about muscle stiffness, contraction time, dominance and type of the muscle fiber, as well as about a potential risk that is present during the performance of a specific sports activity is obtained (Rey et al, 2012a;Alentorn-Geli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%